2020
DOI: 10.7150/thno.35568
|View full text |Cite
|
Sign up to set email alerts
|

RNA Nanotechnology-Mediated Cancer Immunotherapy

Abstract: RNA molecules (e.g., siRNA, microRNA, and mRNA) have shown tremendous potential for immunomodulation and cancer immunotherapy. They can activate both innate and adaptive immune system responses by silencing or upregulating immune-relevant genes. In addition, mRNA-based vaccines have recently been actively pursued and tested in cancer patients, as a form of treatment. Meanwhile, various nanomaterials have been developed to enhance RNA delivery to the tumor and immune cells. In this review article, we summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 203 publications
(186 reference statements)
0
78
0
1
Order By: Relevance
“…mRNA-based therapeutics as well as vaccines hold incredible therapeutic potential and there are currently a number of mRNA-based systems that are progressing to clinical use including mRNA vaccines for COVID-19 [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ]. Previous studies have demonstrated the clinical promise of mRNA for a range of therapeutic applications [ 8 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], proving the utility of mRNA as a powerful immuno-therapeutic platform that can achieve the necessary requirements for safety and scaled-up GMP production [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…mRNA-based therapeutics as well as vaccines hold incredible therapeutic potential and there are currently a number of mRNA-based systems that are progressing to clinical use including mRNA vaccines for COVID-19 [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ]. Previous studies have demonstrated the clinical promise of mRNA for a range of therapeutic applications [ 8 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], proving the utility of mRNA as a powerful immuno-therapeutic platform that can achieve the necessary requirements for safety and scaled-up GMP production [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various non-coding RNAs were identified and may be a novel biomarker gene set for evaluating the shRNA-based antitumor treatment via skin administration or intramuscular injection. RNA technology-mediated cancer immunotherapies have been applied in preclinical studies and clinical trials [ 6 , 44 ]. Even though the route of administration for RNA technology-mediated cancer immunotherapies is different from our present study, our finding provides a novel biomarker gene set for these RNA-based cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligonucleotide drugs and small interfering RNA (siRNA)-based drugs are approved to treat spinal muscular atrophy, Duchenne muscular dystrophy, and hereditary transthyretin-mediated amyloidosis [ 4 , 5 ]. Moreover, targeting the immune inhibitory genes via siRNA or short-hairpin RNA (shRNA) can induce immune responses against cancers [ 6 , 7 ]. However, the molecular level mechanisms in siRNA/shRNA-targeted immune cells, and the biomarkers for evaluating the therapeutic effect, are not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Functional nanomaterials with lysosome escaping ability have been widely reported; these nanomaterials are favorable for antigen delivery to the cytoplasm and their intracellular digestion, which further contributes to antigen processing and presentation (Jiang et al, 2018;Zhong et al, 2019). Lipid-based nanoparticles and polymeric nanoparticles (Reichmuth et al, 2016;Zhou et al, 2016;Gulla et al, 2019;Wen et al, 2019;Lin et al, 2020), with better biocompatibility, have been reported in the development of DC targeted vaccines for anticancer and antiviral treatments. Liposome-based nanoparticles containing molecules such as trivalent influenza antigen, OVA, and heat shock proteins, have been investigated for their ability to activate the immune system in disease treatment.…”
Section: Manipulation Of Dcs For Vaccinationmentioning
confidence: 99%